Number Head Together Co-operative Learning Model to Improve Student Learning Quality at MAN Pulau Taliabu - Adiyana Adam; Pardin, Pardin (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
Through the numbered head together learning strategy, it is hoped that students will actively work together in small groups, discuss answers with group members and ensure that each group member can work on and know the answer, so that through this learning strategy can increase student learning activity. The numbered head together learning strategy can be optimal, it needs to be supported by the use of effective learning media. This study used a qualitative approach with a descriptive research type. Data collection techniques in this study were observation, interviews, questionnaires and documentation. Data analysis in research uses qualitative descriptive techniques through three stages, namely: data presentation, data reduction and verification or drawing conclusions. Based on the discussion and analysis of data proving that using the Numbered Heads Together (NHT) model in Economics Class XII MAN Pulau Taliabu, it can be concluded that: Using the Numbered Heads Together (NHT) model in Economics subjects increases the learning interest of Class XII MAN Island students Taliabu This can be seen from the indications of interest in learning at each meeting.